Evaluation of isometric strength in people with spinal cord injury: a review - Lima, Jamile Ada Nascimento de; Oliveira, Saulo Fernandes Melo de; Oliveira, Lúcia Inês Guedes Leite de; Costa, Manoel da Cunha (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: isometric muscle strength in people with spinal cord injury is usually associated with locomotor activity, posture maintenance and activities of daily living. However, the variety of methods available for the evaluation hinders decision making on the part of the professionals involved. Objective: our objective was to review the literature of the area and determine the evaluation methods of isometric force and relationships with other components of health and physical fitness of people with spinal cord injury (SCI). Methods: consulted if the sites BIREME-Medline and SciELO, under the terms “spinal cord injury”, “paraplegia”, “tetraplegia”, “wheelchair athletes” and “disabilities athletes,” “isometric strength”, “handgrip” and “ handheld “with the help of the Boolean AND operator. Results: they were found 18 studies that met the inclusion criteria. The equipment available, the manual dynamometer is the most used. Sophisticated equipment can evaluate force components with increased functionality. There were no significant changes in hemodynamic variables during isometric strength tests. In conclusion, good isometric strength levels appear to correlate with increased functionality of people with SCI. Conclusion: however, they are lacking reference values related to the isometric strength for this population, especially when tested handgrip.